The importance of upper gastrointestinal endoscopy in morbidly obese patients - Baysal, Birol; Kayar, Yusuf; Danalıoğlu, Ahmet; Özkan, Tuba; Bayram Kayar, Nuket; Ünver, Nurcan; Bozkurt, Süleyman; İnce, Ali Tüzün (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Obesity is an epidemic and its prevelance and number of patients underwent bariatric surgery continue to increase worldwide. This study aimed to evaluate endoscopic findings and co-morbidities, to investigate the prevelance of Helicobacter pylori (H. pylori) infection and the relationship between body mass index (BMI) and gastroesophageal sphincter incompetency in obese patients. Materials and Methods: An upper gastrointestinal system endoscopy and mucosal sampling were performed in all patients hospitalized for bariatric surgery. Age, gender, BMI, co-morbidities and endoscopic findings were recorded. Gastroesophageal sphincter incompetency was classified according to Hill classification. The patients were divided into two groups: group I, endoscopically normal and group II, endoscopically abnormal. Results: Total 127 patients were enrolled into prospective study. Of these, 93 (%73.2) were female and the mean age was 38.9±12.5 years (range: 16-68). Abnormal endoscopic findings and H. pylori were detected in 80.4% and 44.9% of patients, respectively. In group II, patients were older, BMI higher and H. pylori more prevalent (all statistically significant). Diabetes mellitus, hypertension and dyslipidemia were the most frequent common co-morbidities. Rate of multiple co-morbidities were more common in group II. Gastroesophageal sphincter incompetency in total group was observed in a rate of 46.5% and was weakly correlated with BMI. Conclusion: Four-fifths of obese patients have at least one endoscopic abnormal finding, three fourth at least one co-morbidity and half H. pylori positivity. Upper gastrointestinal system endoscopy should be performed routinely in all patients to predict and prevent complications following bariatric surgery.